1979
DOI: 10.1177/0013916579112004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Cognitive Representations of Spatial Relationships

Abstract: Samples of subjects from three different residential locations were asked to indicate their knowledge of the same environment by (a) estimating the distances between pairs of geographic locations and (b) arranging markers on a "map-board" to represent the locations and the distances between them. Comparisons of the results between methods revealed striking differences which lead to discrepant and even contradictory conclusions about the impact of residential location on cognitive representations of distance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…This is consistent with previous studies, which have found the exponent to be 1 or slightly less than 1 for perceived distance along the ground (Da Silva, 1985;Wagner, 1985;Wiest & Bell, 1985). Linear functions (exponents close to 1) are also found when subjects estimate from memory the distances between buildings in a familiar campus environment (Baird, Merrill, & Tannenbaum, 1979;Sherman, Croxton, & Giovanatto, 1979). This linear trend differs substantially from the power functions for imaged and recalled distance.…”
Section: Resultssupporting
confidence: 91%
“…This is consistent with previous studies, which have found the exponent to be 1 or slightly less than 1 for perceived distance along the ground (Da Silva, 1985;Wagner, 1985;Wiest & Bell, 1985). Linear functions (exponents close to 1) are also found when subjects estimate from memory the distances between buildings in a familiar campus environment (Baird, Merrill, & Tannenbaum, 1979;Sherman, Croxton, & Giovanatto, 1979). This linear trend differs substantially from the power functions for imaged and recalled distance.…”
Section: Resultssupporting
confidence: 91%
“…The research literature on sketch maps is large and contains findings ranging from metric distortions between sketch maps and actual maps (see Briggs, 1976;Sherman et al, 1979;Buttenfield, 1986), through to peoples' environmental perception (e.g., Downs and Stea, 1973;Moore, 1973;Golledge and Stimson, 1997), to environmental learning theories (e.g., Hart and Moore, 1973;Siegel and White, 1975;Golledge, 1978). The traditional methods used for sketch map analysis, which focus on the final drawing, do not show how the image of a city is acquired, stored and progressively recalled.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We then used this explicitly constructed map as a representation of their cognitive map. Such a technique is relatively common in the spatial cognition literature (see, e.g., Baird et al, 1979;Huertas & Ochaita, 1992;Sherman, Croxton, & Giovanatto, 1979;Waller, 2000;Walsh, Krauss, & Regnier, 1981). Comparisons between participants' explicitly constructed maps and those derived from MDS and other scaling techniques can inform us about the relative ability of these techniques to represent peoples' cognitive maps.…”
Section: Mds In Spatial Cognition Researchmentioning
confidence: 99%